Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/mcda.1696
|View full text |Cite
|
Sign up to set email alerts
|

A possibility distribution‐based multicriteria decision algorithm for resilient supplier selection problems

Abstract: Thus far, limited research has been performed on resilient supplier selection-a problem that requires simultaneous consideration of a set of numerical and linguistic evaluation criteria, which are substantially different from traditional supplier selection problem. Essentially, resilient supplier selection entails key sourcing decision for an organization to gain competitive advantage. In the presence of multiple conflicting evaluation criteria, contradicting decision makers, and imprecise decision relevant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…The comprehensive reliability is computed by the product of the two index, and the reliability-based membership function are fused using Dempster's combination rule (Dempster, 1967;Wen et al, 2017). The numerical examples provided by Jiang et al (2018) verified the effectiveness of the reliability modification approach in membership functions.…”
Section: Membership Function and Reliability Modificationmentioning
confidence: 82%
See 2 more Smart Citations
“…The comprehensive reliability is computed by the product of the two index, and the reliability-based membership function are fused using Dempster's combination rule (Dempster, 1967;Wen et al, 2017). The numerical examples provided by Jiang et al (2018) verified the effectiveness of the reliability modification approach in membership functions.…”
Section: Membership Function and Reliability Modificationmentioning
confidence: 82%
“…It is true that the existing research have shown promising potential of MCDA methods and fuzzy techniques in supplier selection problems (Gan et al, 2019;Haldar et al, 2012Haldar et al, , 2014Hasan, Shohag, Azeem, Paul, & Management, 2015;Jiang, Faiz, & Hassan, 2018). However, there are limitations of the state-of-the-art literatures: (i) to the best of our knowledge, no existing research extends F-MADM framework in supplier evaluation problems leveraging large number of information (time series and graphical information), (ii) no prior study investigated F-MADM approach for evaluating suppliers' performance from resilience and logistics 4.0 perspective, simultaneously, and (iii) it is not clear how fuzzy based TOPSIS can be extended to process inherent uncertainty in decision relevant information associated with both the quantitative and qualitative attributes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplier evaluation is an important decision-making problem that strongly affects the quality, efficiency and reliability of a supply chain [14]. There are often complex problems encountered in the selection of suppliers, including the many criteria against which suppliers can be evaluated, of which, some can be very specific.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, the decision problem involves weighting several structural system alternatives against these conflicting criteria, which becomes more complicated when evaluation is done by multiple decision makers. Multi-criteria decision making (MCDM) methods are one of the most promising approaches used to solve these complex decision problems (Jiang et al 2019).…”
Section: Introductionmentioning
confidence: 99%